When "Comoners were made slaves by the magistrates": The 1627 election and political culture in Norwich - WILLIAMSON, Fiona (Institutional Knowledge at Singapore Management University, 2017)
This article tells the story of a contested provincial election for sheriff which took place in Norwich during 1627. In light of recent scholarly critiques of studies that frame the early-modern period in terms of binary opposites, this article demonstrates that 1620s political culture is hard to define in such stark terms. Through a close reading of the events, characters, and outcomes of the election, this article also shows the importance of embedding local peculiarities into wider historiographical narratives of change, or continuity, and reveals the essential role of the urban middling sorts in shaping the political narratives of the Stuart period.